Nanocrack formation in AlGaN/GaN high electron mobility transistors utilizing Ti/Al/Ni/Au ohmic contacts. (March 2017) - Whiting, P.G.; Rudawski, N.G.; Holzworth, M.R.; Pearton, S.J.; Jones, K.S.; Liu, L.; Kang, T.S.; Ren, F.
Abstract: AlGaN/GaN HEMTs are poised to become the technology of choice in RF and power electronics applications where high operating frequencies and high breakdown voltages are required. The alloyed contacting scheme utilized in the formation of the source and drain contacts of these devices affects the conduction of electrons through the 2DEG from the moment of ohmic contact formation onward to operation in the field. Analysis of the ohmic contacts of as-fabricated and electrically stressed AlGaN/GaN HEMTs, via chemical deprocessing and Scanning Electron Microscopy, indicates the presence of cracks oriented along the [11-20] directions, which nucleate at metal inclusions present under the alloyed ohmic source/drain contact metal. Cracks which form at the edges of these contact regions can extend into the channel region. It appears that electrical biasing induces additional growth in the longest cracks present within the channel regions of these devices. Highlights: SEM of deprocessed AlGaN/GaN HEMTs, as-formed, reveals cracks in the AlGaN. Cracks form at the ohmic contact inclusions and are oriented along the [11-20] directions. A model for crack formation and propagation into the HEMT channel has been developed. Off-state stressing appears to induce lengthening of cracks due to inverse piezoelectric strain.